Did pandemic relief fraud inflate house prices? - Griffin, John M.; Kruger, Samuel; Mahajan, Prateek (Journal of Financial Economics, 2026)
Pandemic fraud is geographically concentrated and stimulated local purchases, with effects on prices. Recipients of fraudulent Paycheck Protection Program (PPP) funds significantly increased their home purchasing rate compared to recipients of non-fraudulent PPP funds, and house prices in high-fraud ZIP codes increased 5.8 percentage points more than in low-fraud ZIP codes within the same county. In a horse race, pandemic fraud is one of the largest and most robust factors explaining house price appreciation during COVID. ZIP codes with fraud also experienced heightened vehicle purchases and other consumer spending in 2020-21, with a return to normal in 2022.